Kedudukan Hukum Hipotek Kapal Laut Dalam Hukum Jaminan Dan Penetapan Hipotek Kapal Laut Sebagai Jaminan Perikatan - Syukri Hidayatullah, S.H., M.H (Law Department, University of Widya Gama Mahakam Samarinda, 2015)
Given the importance of the position of fund's credit in the development process, it has been supposed to be the giver and the recipient of the credit and other related parties are protected through a rights institutions, strong guarantee and also be able to provide legal certainty for all parties concerned in the various sectors of the trade of Indonesia, including the shipping sector. To encourage the shipping industry, the Government has undertaken various legal actions including through deregulation in the field of sea transport issued Law No. 17 in 2008 about voyage, the President’s Instruction Number 5 in 2005 concerning Empowerment National Shipping Industry and the regulation of President No. 44 in 2005 about ratification of the International Convention on Maritime Receivable and Mortgage with this ratification, particularly the field of shipping, the Indonesian shipping industry may participate empower and strengthen national and international efforts to prepare Legislation in the draft of Law on the Maritime Claim Prior and Mortgages on Ships. The regulations of ship mortgage, among others, are still adopting colonial rule both the Book of the Law of Civil Law (Civil Code) and the Book of the Law of Commercial Law (Commercial code) and Indonesia legislation, namely Law No. 17 in 2008 about Shipping. Regarding the distribution of these regulations will be further discussed in Chapter II.